The Effect Of Woolwich Massage On The Slowness Of Breast Milk Production In Public Mothers : EVIDENCE BASED CASE REPORT (EBCR): PENGARUH PIJAT WOOLWICH TERHADAP KELANCARAN PRODUKSI ASI PADA IBU NIFAS - Jen Astika Nuari; Hidayati, Desi; Sofiyanti, Santi (Jurnal Kesehatan Siliwangi, 2024)
Background: Exclusive breast milk is pure breast milk without additional food or additional fluids such as formula milk, water, etc. which is given to newborn babies before the baby is 6 months old. Woolwich massage has several benefits, including increasing prolactin and oxytocin reflexes (let down reflex), preventing blockages, increasing breast milk production and preventing inflammation or breast dams.. Objective: To determine out that giving Woolwich massage can lead to smooth breast milk production for postpartum mothers. Method: The method for writing this EBCR is by searching for evidence through data based Pubmed and Google Scholar with the publication year 2018-2023, 4 articles were obtained for critical review. Results: After evaluation before and after the Woolwich massage, the mother's breast milk production became smooth.. Conclusion: Giving Woolwich massage is effective in helping to facilitate breast milk production.